SYNERGETIC FEATURES OF THE SPIRITUAL HERITAGE OF RENAISSANCE THINKERS - Jafar Mustafayev (European Journal of Interdisciplinary Research and Development, 2023)
This scientific article discusses the relevance of studying the culture of the medieval East in the era of globalization. She emphasizes the importance of the full development of wealth and the effective use of humanistic ideas represented by the spiritual heritage of the Middle Ages. The article also examines the relationship between the existence of spiritual heritage and the viability of the external environment, and also highlights the role of the human factor in shaping this process. Examples of the negative consequences of attempts to destroy the cultural and spiritual heritage are given, and the importance of maintaining the connection of peoples with their past is described.